SPEAKING CLASS IN HIGHER EDUCATION - Yani Awalia Indah; Ihda ‘Abidat; Meita Lesmiaty Khasyar (STKIP PGRI Jombang, 2021)
In recent years the process of reform and innovation in higher education has been witnessed. Indonesia has also implemented the problem of based assessment almost throughout college in the fatherland, focusing on human resource development. Methods adopted to follow the qualitative study principle against ten students at one of the schools in Bogor. This research is limited to the students without even seeing the washback effect on the teachers. The objective of this report was to observe the washback effect during teaching activities in a spoken English class. The study proved that a student's point of view assessment affects the teaching process and the speaking skills in the classroom.